2003
DOI: 10.1524/zkri.218.12.802.20544
|View full text |Cite
|
Sign up to set email alerts
|

Structure of iron-rich compounds in the Yb–Fe–Al system

Abstract: X-ray diffraction studies on eleven single crystals having compositional ratios close to Yb/(Fe,Al) = 2:17 revealed four distinctly different structures, two having hexagonal symmetry (LuFe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The amount of ternary 2/17 phases is in the range of 40-98 wt.%. Compared to the aluminum containing system Yb-Fe-Al which was studied at the same equilibrium temperature of 500 • C [3,4] the homogeneity ranges of the H2/17 and R2/17 phases are smaller: LuFe 9.5 type: 0-28 at.% Ga; PrFe 7 type: 16-35 at.% Ga. Similar to the aluminum system, the H1/7 phase occurs in as cast samples only and disappears during the annealing at 500 • C. In contrast to the aluminum system, however, a tetragonal phase with ThMn 12 type structure is not observed in the compositional region investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of ternary 2/17 phases is in the range of 40-98 wt.%. Compared to the aluminum containing system Yb-Fe-Al which was studied at the same equilibrium temperature of 500 • C [3,4] the homogeneity ranges of the H2/17 and R2/17 phases are smaller: LuFe 9.5 type: 0-28 at.% Ga; PrFe 7 type: 16-35 at.% Ga. Similar to the aluminum system, the H1/7 phase occurs in as cast samples only and disappears during the annealing at 500 • C. In contrast to the aluminum system, however, a tetragonal phase with ThMn 12 type structure is not observed in the compositional region investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The data were collected on SNBL at ESRF (Grenoble, France) and analyzed by using the FullProf Suite software [7]. The structure models used for the hexagonal and orthorhombic phases were that reported in [3,4]. The site occupancies of ytterbium which is partially substituted by mixed Fe/Ga dumbells were constrained with respect to their sums (Yb + (Fe/Al) 2 = 100%) but left unconstrained with respect to the overall compositional ratios Yb/(Fe/Al) 2 of the crystals.…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ytterbium‐containing materials have not yet been studied in great detail, because of problems with sample preparation. Recently structural and magnetic properties of aluminum‐substituted compounds of composition Yb 2− x (Fe,Al) 17+2 x have been investigated2, 3 and structural features of some gallium analogues Yb 2− x (Fe,Ga) 17+2 x have been reported 4. All compounds were found to be ferromagnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Single‐crystal laboratory X‐ray data have shown that in 1 and 2 the rare‐earth atoms are partially substituted by Fe 2 dumbbells and vice versa, and that the Fe atoms are partially substituted by Al or Ga atoms 2. 3, 4 The resolution of the data and limitations of the conventional structure determination technique, however, did not allow other structural details to be well characterized, such as stacking faults and possible compositional inhomogeneities along [001]. Consequently, the purpose of the present work was to characterize the structure of gallium crystals by means of a high‐resolution synchrotron diffraction measurements with a newly developed computer program that allows several structures to be refined on one single crystal data set 7.…”
Section: Introductionmentioning
confidence: 99%